Pelapisan Benih dengan Aktinobakteri untuk Meningkatkan Pertumbuhan Tanaman Padi: Actinobacterial Seed Coating for Promoting Rice Plant Growth - Elisa Sopiatul Fitriani; Zaenal Abidin; Yulin Lestari (Departemen Biologi, Institut Pertanian Bogor, 2023)
The need for rice continues to increase along with the increase in population. Efforts to increase rice production is generally carried out through proper and balanced fertilization. Other than that, plant growth-promoting actinobacterial (PGPB) inoculants can be used as an alternative solution. This study aimed to examine the effect of the application of actinobacterial seed dressing and NPK fertilizers on the growth of rice plants grown in a glass house. A randomized block design with three factors was conducted, consisting of actinobacterial seed dressing (added and not added), type of carrier (zeolite, peat, and combinations) and doses of NPK fertilizer (0 g/pot, 0.375 g/pot, and 0.75 g/pot). The addition of actinobacteria consortium, peat-zeolite combination 1:3, and NPK fertilizer at a dose of 0.75 g/pot (A2C3P3) gave consistent results in increasing the average yield of rice vegetative and reproductive parameters observed in the glass house. The A2C3P3 treatment had a significant effect on the number of tillers, width of flag leaf, dry weight of roots and shoots of rice observed at 10 WAP compared to other treatment combinations. The actinobacterial seed coating plays a pivotal role in supporting rice plant growth.